Histomorphometric analysis of rat alveolar wound healing with hydroxyapatite alone or associated to BMPs - Brandão Alexandre C.; Brentegani Luís Guilherme; Novaes Jr. Arthur B.; Grisi Márcio Fernando M.; Souza Sérgio Luís Scombatti de; Taba Jr. Mario; Salata Luiz Antônio (Fundação Odontológica de Ribeirão Preto, 2002)
Several materials and techniques have been proposed to improve alveolar wound healing and decrease loss of bone height and thickness that normally follow dental extraction. The objective of this research was the histologic analysis of bone morphogenetic proteins implanted into dental alveoli of rats after extraction. A total of 45 adult male Wistar rats were divided into three groups of 15 animals each: control (no treatment), implanted with pure hydroxyapatite (HA, 3 mg) and implanted with hydroxyapatite plus bone morphogenetic proteins (HA/BMPs, 3 mg). Five animals from each group were sacrificed at 7, 21 and 42 days after extraction for the histometric analyses of the osteoconductive potential of hydroxyapatite associated or not with BMPs. After dissection, fixation, decalcification and serial microtomy of 6-mm thick sections, the samples were stained with hematoxylin-eosin for histologic and histometric analyses. Both HA and HA/BMPs caused a delay in wound healing compared to control animals, evaluated by the percentage of bone tissue in the alveoli. The treatment with HA/BMPs had the greatest delay at 21 days, even though it produced values similar to the control group at 42 days. The materials did not improve alveolar repair in the normal period of wound healing and the association of HA/BMPs did not have osteoconductive properties with granulated hydroxyapatite as the vehicle.